Nutrient recovery and reproductive potential of Eisenia fetida during the vermicomposting of organic waste with cow dung - Amrit Kumar; Mayank Kumar; Neeraj Panday; Nitin Kamboj; Himanshu Saini (Environment Conservation Journal)
The current study reveals that vermicomposting garden waste (GW) and kitchen waste (KW) is a highly effective eco-biotechnological method for converting garden waste (GW) and kitchen waste (KW) into cow dung using Eisenia fetida. This technique is both excellent and environmentally friendly. In this study, we utilized cow dung (CD) as the initial feeding stock, along with various composting materials. The experiment was conducted in the spring season in different ratios of both waste [garden waste, marking as G1, G2, G3, and K1, K2, K3] with cow dung for 65 days. The changes in PWC, growth rate, and HPR in different ratios of both garden and kitchen waste were significantly different compared to the CD. The changes in PWC of diIt was found that the changes in PWC for different amounts of garden waste were significantly different from the CD in terms of growth rate (F3,8: 47.16; p < 0.0001; one-way ANOVA), HPR (F3,8: 4.45; p = 0.041; one-way ANOVA), and the same was true for kitchen waste. The changes in PWC for different amounts of kitchen waste were significantly different from the CD in terms of growth rate (F3,8: 164.8; p < 0.0001; one-way ANOVA), and HPR (F3,8: 52.19; p < 0.0001; one-way ANOVA). meters are analyzed during vermicomposting. Earthworm activity significantly reduced pH 0.5 to 2.18 and also decreased organic carbon and organic matter content from 28.9% to 71.3%. After vermicomposting, the total Kjeldahl nitrogen and available phosphorous content significantly increased from 32% to 171% in all mixtures. Moisture content and bulk density both decreased significantly in all mixtures from 10.9% to 81.7%. The results indicated that the G2 and K2 were the best combination for earthworm fecundity and growth rate.